G. Dosi, Ch. Freeman, R. Nelson, G. Silverberg, L. Soete (eds) (1991) Technical Change and Economic Theory, Londres y Nueva York, Pinter Publishers. - Vega-Centeno, Máximo (1993)
La reseña no presenta resumen.